2009
DOI: 10.1007/s11671-009-9379-6
|View full text |Cite
|
Sign up to set email alerts
|

Pd Nanoparticles and Thin Films for Room Temperature Hydrogen Sensor

Abstract: We report the application of palladium nanoparticles and thin films for hydrogen sensor. Electrochemically grown palladium particles with spherical shapes deposited on Si substrate and sputter deposited Pd thin films were used to detect hydrogen at room temperature. Grain size dependence of H2sensing behavior has been discussed for both types of Pd films. The electrochemically grown Pd nanoparticles were observed to show better hydrogen sensing response than the sputtered palladium thin films. The demonstratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(61 citation statements)
references
References 25 publications
1
60
0
Order By: Relevance
“…The PVD/CVD was covered with a layer of porous carbon and create a filter for some compounds, such as CO. For hydrogen, such coating does not be barrier but compounds such as carbon monoxide have difficult access to parts of the palladium films. It can be important for sensor functioning in an atmosphere such as CO, which poisons the detector and usually gives changing the electrical conductivity of the active layer [27,32,33]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PVD/CVD was covered with a layer of porous carbon and create a filter for some compounds, such as CO. For hydrogen, such coating does not be barrier but compounds such as carbon monoxide have difficult access to parts of the palladium films. It can be important for sensor functioning in an atmosphere such as CO, which poisons the detector and usually gives changing the electrical conductivity of the active layer [27,32,33]. …”
Section: Resultsmentioning
confidence: 99%
“…Porous carbon has a high specific surface area [23], which suggests that the combination of these characteristics will significantly increase the possibilities of detection and makes these films ideal sensors of the hydrogen. It also showed that the nanocrystalline palladium can absorbs hydrogen [24,25], it can show a change in crystal structure [26] and in electrical conductivity [27] in hydrogen presence.…”
Section: Introductionmentioning
confidence: 95%
“…Another third port was provided for vacuum gauge connection. A multi-pin feedthrough at the base of the chamber allowed for the electrical connections to be established to the heater assembly as well as to the sensor electrodes via spring loaded pins [19][20][21].…”
Section: Methodsmentioning
confidence: 99%
“…In thinking about how these results relate to previous Schottky diode-based hydrogen detectors we consider the response time, sensitivity and other features. First of all, the initial time response is slow, as is the case with some other investigations using Schottky diodes [31,32,54], and even some work on hydrogen detection using Pd nanoparticles and thin films [55], but once the detector has been 'sensitized' the response to subsequent changes in hydrogen level is somewhat faster, on the scale of minutes. There are two aspects to the slow initial response, the first being that hydrogen must reach the SB interface region where it interacts to cause a lowering of the barrier.…”
Section: Hydrogen Detectionmentioning
confidence: 97%